WHO IS RESPONSIBLE FOR THE CONSEQUENCES? A CASE OF STENT THROMBOSIS SUBSEQUENT TO NONCOMPLIANCE WITH POST ANGIOPLASTY TREATMENT REGIMEN - Sajwani, Salma Abdul Aziz; Allana, Saleema (Journal of Ayub Medical College Abbottabad, 2014)
Coronary artery disease (CAD) is a major cause of mortality internationally and inPakistan. Angioplasty has been proven to be an effective treatment for CAD. Stent thrombosis is a known but preventable complication of angioplasty. Several factors may lead to stent thrombosis with non-compliance with the prescribed drug regimen, being one of the most important factors. We report a case of stent thrombosis after four months of angioplasty. After exploring of patient's post angioplasty routines, it was found that the patient was non-compliant with the prescribed anti-platelets and other prescribed drugs. This time the patient presented with another acute myocardial infarction, and he went through angioplasty again. Keywords: Coronary artery disease, Angioplasty, Stent thrombosis, Non-compliance with medications